Poverty in Capitalism. Why is it Persisting Today? (2013)
The purpose of this paper is to provide elements to reflect on the way poverty is nowadays conceptualized and on its causing factors -- This paper discusses that a classic-neoclassical frame of reference cannot explain the persistence or increase of poverty in today's developed countries -- This article suggests that through a Marxist historic-descriptive and theoretical-logical method it may be possible to gain understanding about poverty in capitalism and its current evolution